Experimental investigation of time delays data transmission in automatic control systems - Ryabenkiy, Vladimir Mikhailovich; Ushkarenko, Alexander Olegovich (My University, 2015)
The method of statistical analysis of time-delay transmission of information and control packets over the network in automatic control systems are considered in this article. The results of measurements of time delays, which are obtained based on the analytic dependence of the probability density allow theoretically determine the time delays for datatransmission.
Ryabenkiy, V. M. Experimental investigation of time delays data transmission in automatic control systems / V. M. Ryabenkiy, A. O. Ushkarenko // Problems of Information Technologies. – 2015. – № 1 (017). – P. 42–45.
Keywords: statistical analysis; time delay; hystogram; probability density